2006
DOI: 10.4269/ajtmh.2006.74.322
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cryptosporidium and Other Enteric Parasites Among Wild Non-Human Primates in Polonnaruwa, Sri Lanka

Abstract: Cryptosporidiosis is a rapidly emerging disease in the tropics. This is the first report of Cryptosporidium and other protozoan infections (Entamoeba spp., Iodamoeba, Chilomastix, and Balantidium spp.) in wild primates that inhabit the natural forest of Sri Lanka. It is unclear if non-human primates serve as a reservoir for these parasites under certain conditions. A cross-sectional coprologic survey among 125 monkeys (89 toque macaques, 21 gray langurs, and 15 purple-faced langurs) indicated that Cryptosporid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 29 publications
5
54
1
3
Order By: Relevance
“…Although a prior meta-analysis of primate parasite diversity failed to find a substrate effect [64], other studies have reported lower parasite prevalence in arboreal primates compared to sympatric terrestrial primates [92][93][94]. These studies did not, however, account for disparities in home range size, which may influence exposure to microorganisms [95].…”
Section: Discussionmentioning
confidence: 99%
“…Although a prior meta-analysis of primate parasite diversity failed to find a substrate effect [64], other studies have reported lower parasite prevalence in arboreal primates compared to sympatric terrestrial primates [92][93][94]. These studies did not, however, account for disparities in home range size, which may influence exposure to microorganisms [95].…”
Section: Discussionmentioning
confidence: 99%
“…Further, local farmers graze their cattle in the sanctuary. The researchers showed that infection with the apicomplexan protozoan Cryptosporidium (causing the diarrheal illness cryptosporidiosis in humans) was higher in purple-faced langur groups using areas and water that had been heavily soiled by human feces and livestock (Ekanayake et al 2006). Work in the more urbanized parts of the purplefaced langur's range highlighted some of the other dangers of living too close to humans, with langurs being killed by electrocution and guard dogs, or by traffic while crossing roads (De Silva et al 2011;Parker et al 2008).…”
Section: Adaptations To Human-modified Environmentsmentioning
confidence: 99%
“…Researchers at the Polonnaruwa Archeological Sanctuary investigated the gastrointestinal parasites in a population of purple-faced langurs (Dewit et al 1991;Ekanayake et al 2006Ekanayake et al , 2007. Parts of the sanctuary are subject to a continuous flow of local pilgrims and tourists, who, along with local residents, use areas near water as open toilets, for picnicking, and for disposal of food waste.…”
Section: Adaptations To Human-modified Environmentsmentioning
confidence: 99%
“…Snares set for bush meat trap other animals, including leopards (Kittle et al 2014). Humans and their domestic animals also have introduced disease, such as toxoplasmosis (Ekanayake et al, 2004), cryptosporidiosis and a variety of enteric parasites into wild populations of primates (Ekanayake et al, 2006(Ekanayake et al, , 2007.…”
Section: Human-animal Conflict and Misconceptionsmentioning
confidence: 99%